History of Islamic Education in the Modernization Era of Egypt - Cici Cahyani Cici; Banu Irfan (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2022)
The purpose of this writing is to discuss Islamic education in the modernization era of Egypt. This paper concludes that modernization in Egypt began with the arrival of Napoleon Bonaparte in Alexandria in Egypt on July 2, 1798 M. Napoleon's expedition to Egypt besides bringing a strong army also brought scientists with a set of scientific equipment to conduct research, see progress in science and technology In France, this provided inspiration for Egyptian figures to make changes, one of the popular figures as Islamic renewal in Egypt was Muhammad Ali Pasha and Jamaludin Al-Afghani. The strategy for reforming Islamic education carried out by a number of reformers in Egypt is as follows: Establishing the ministry of education and school education institutions, Sending Egyptian students to study in the West, Expanding access to education, Organizing the system and structure of educational institutions, Integrating the educational curriculum, Creating new innovations in educational methods.